PENCEGAHAN ANEMIA PADA IBU HAMIL - Ardie Pratama, Ardie Pratama; Ratnasari, Febi; Harahap, Ardika Tri Nanda; Astuti, Diah Ayu; Agustin, Imelda; Hardiyanti, Intan Putri; Leosae, Merdi Mesio Nardi; Permana, Mochamad Dani; Anggrayni, Nuke; Arsita, Rachmah Dara; Darmawangsah, Saputra; Hopipah, Sri (Nusantara Hasana Journal, 2022)
Anemia is a nutritional problem that needs attention and becomes one of the health of the Indonesian people experienced by all age groups ranging from toddlers, adolescents, pregnant women, to old age. Based on Riskesdas in 2018 presentation of pregnant women suffering from anemia by 48.9% or about 5 out of 10 pregnant women in Indonesia suffer from anemia. The purpose of this activity is to find out the level of knowledge about anemia and how to prevent anemia in pregnant women. Methods used lectures, practice, fill out posts and pre-tests, Q&A. The population taken is sabur women and pregnant women. The result of this activity is that the patient is able to know what are the ways to prevent anemia in pregnant women.